Biological aspects of slipper lobster (Thenus orientalis) on West Coast of Sabah, Malaysia (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Teoh C-F, Yong AS-K, Ihsan YN, Sahari NSB, Alvicius A, Radzi IHB, Tuzan AD. 2025. Biological aspects of slipper lobster (Thenus orientalis) on West Coast of Sabah, Malaysia. Biodiversitas 26: 1443-1452. Thenus orientalis, a highly sought-after Scyllaridae species, is a promising aquaculture candidate. The acquisition of reliable fishery statistics is critical to reducing overfishing risks and understanding its biological aspects, ensuring long-term viability and sustainable practices. This study analyzed the biological characteristics of sex composition, monthly sex ratio, and size frequency distribution of 922 T. orientalis (473 males and 449 females; 47.24-99.02 mm Carapace Length; CL) collected at bimonthly intervals of 10 months from April 2019 to January 2020 from the West Coast of Sabah, Malaysia and the reproductive biology of ovarian maturation stages, Gonadosomatic Index (GSI) and size at first maturity of 179 females (46.24-82.66 mm CL), has practical implications for aquaculture. The overall sex ratio was found to be 1:0.95 (?²: 0.54, P=0.46), with the highest abundance of males sampled between November and December. Thenus orientalis is distributed with an average size of approximately 64.14 mm CL, with males dominating smaller size classes (
Keywords: Ovarian development, reproductive biology, slipper lobster, Thenus orientalis, West Coast of Sabah